Effect of compound inoculants Ti and Zr on as cast microstructure and mechanical properties of Al–Cu alloy. (May 2014) - Zheng, Q.; Yang, C.; Wang, S.; Yu, A.; Chen, H.; He, Y.
Abstract : Control of as cast grain size is important for Al–Cu alloys and always achieved by inoculation. In this paper, the microstructure and mechanical properties of Al–Cu alloy were investigated by adding compound inoculants Ti and Zr. The results show that the refinement effect of Ti and Zr is compatible in the Al–Cu alloy. Al3 Ti and Al3 Zr were formed in Al–Cu alloy with additions of a little Ti and Zr, which respectively provided the heterogeneous nucleation sites for α-Al. Intermetallic aluminised dispersions Al3 (Ti, Zr) were formed with additions of large amounts of Ti and Zr in Al–Cu alloy, which accelerated the heterogeneous nucleation of α-Al and resulted in refining grains of the Al–Cu alloy, so the tensile strength and elongation of Al–Cu alloy were increased. With the synthetical addition of w (Zr) = 0·5% and w (Ti) = 0·3% in the Al–Cu alloy, the tensile strength of Al–Cu alloy reached 174·11 MPa and elongation rate reached 6·20%.